TINGKAT KEPUASAN KUALITAS PELAYANAN PENUMPANG MIKROLET GDI KOTA SURABAYA - TIARA, SANDHI (Swara Bhumi, 2017)
Abstract In a big city like Surabaya there are many kinds of public transportations that can be chosen from. In reality these public transportations which are provide aren’t the main alternative for riding. The change of style in the society caused a group of people to think that public transportation is secondary. We can’t deny this fact for the service quality which are given by them is far from the standard. For them transportation is no longer to get from point A to point B but they also bought the service quality which are speed, comfort, safety and security. Mikrolet which has the most vehicle is G Mikrolet with 312 vehicles. G Mikrolet has a route from Joyoboyo Terminal to Karangpilang to Lakarsantri. This G Microlet has decreased its number of passengers. This can be known from the condition of G Mikrolet during the operation there are many empty seats or doesn’t meet the quota for the seats provided. Five dimensions of service quality in this case reliability, responsiveness, empathy and assurance for the passenger satisfaction G mikrolet in the city of Surabaya. This goal is achieved if the quality of service G mikrolet become better. This research uses survey method. The number of samples in this study is 50 passengers. Data collection was obtained through interviews, observation and documentation. Data analysis technique using descriptive quantitative method. This research uses survey method. Population in this research is all passenger of G mikrolet users in Surabaya City. The sample used for the study is the passengers determined by Accidental Sampling method and limited the number of 50 respondents. Sources of data in this study using primary and secondary data sources. Data collection is obtained through observation, interview and documentation. Data analysis technique using descriptive quantitative method with Likert scale scoring The results of the study showed that passenger satisfaction of the quality of service of G mikrolet in Surabaya City which are felt by passengers was the quality of the reliability of G mikrolet in serving accurately and reliably in serving, the responsiveness given by the driver in serving quickly and precisely and the guarantee felt by the passengers is good. While the satisfaction of the passengers on the quality of empathy services that are felt is still not met because the drivers are not giving sincere attention and are individual, as well as the quality of physical evidence service that has not been met well because of the condition of the fleet facility of the less good mikrolet.   Keywords: Satisfaction, Quality of Service, Microlet